PENGARUH TEGANGAN IMPULS LEWAT DENYAR PADA ISOLATOR KERAMIK TERSUSUN SERI - , HARLIAN SETIADI; , Prof. Dr. Ir. T. Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
e Impulse voltag has a very fast period and a very large peak voltage. This study aims to determine the effect of impulse voltage flashover to the number of series arrangement of a ceramic suspension insulators . Testing was done by giving impulse voltage to ceramic insulators on each series arrangement from 1 until 6. Sphere spark gap was set to produce impuls voltage value . Waveforms were observed on the oscilloscope . When the waveform was perfect, then no flashover occurs , but when the waveform was cut at the tail so the voltage value causing the insulator flashover happened. It is showed that the value of flashover voltage when used one series insulator is 195,62 kV, two series is 420,27 kV, three series is 578,03 kV, four series is 691,62 kV, five series is 813,41 kV, and six series is 923,73 kV. From the experiment it can be obtained that more the number of ceramic insulators connected in series the higher was the impulse flashover voltage value.